Thermodynamics and the Unruh effect - Borges, Lucas Aurélio de Oliveira (2020)
A uniformly accelerated detector perceives the Minkowski vacuum as a thermal state. In particular, for a massless scalar field, one cannot distinguish these two scenarios -accelerated detector in the vacuum and an inertial detector in contact with a thermal reservoir- just by using a point-like detector. In this work we show that one can probe the existence of acceleration by using an extended detector with dimension perpendicular to the acceleration direction. Also, we verify that the internal degrees of freedom of the detector may get entangled by a process of spontaneous emission, and as such is dependent on the initial state of the detector. It is found that the entropy production and entropy fluxes from out the detector also allow one to tell the two scenarios apart: more internal entangled detectors produce less entropy and vice-versa; the wavelength of the sought particle is the critical length at which the behavior of the two system is inverted.